Importance and Challenges of Electrochemical in Situ Liquid Cell Electron Microscopy for Energy Conversion Research - Hodnik, Nejc; Dehm, Gerhard; Mayrhofer, Karl (Accounts of Chemical Research, 2016)
The foreseeable worldwide energy and environmental challenges demand renewable alternative sources, energy conversion, and storage technologies. Therefore, electrochemical energy conversion devices like fuel cells, electrolyzes, and supercapacitors along with photoelectrochemical devices and batteries have high potential to become increasingly important in the near future. Catalytic performance in electrochemical energy conversion results from the tailored properties of complex nanometer-sized metal and metal oxide particles, as well as support nanostructures. Exposed facets, surface defects, and other structural and compositional features of the catalyst nanoparticles affect the electrocatalytic performance to varying degrees. The characterization of the nanometer-size and atomic regime of electrocatalysts and its evolution over time are therefore paramount for an improved understanding and significant optimization of such important technologies like electrolyzers or fuel cells. Transmission electron microscopy (TEM) and scanning transmission electron microscope (STEM) are to a great extent nondestructive characterization tools that provide structural, morphological, and compositional information with nanoscale or even atomic resolution. Due to recent marked advancement in electron microscopy equipment such as aberration corrections and monochromators, such insightful information is now accessible in many institutions around the world and provides huge benefit to everyone using electron microscopy characterization in general.Classical ex situ TEM characterization of random catalyst locations however suffers from two limitations regarding catalysis. First, the necessary low operation pressures in the range of 10(-6) to 10(-9) mbar for TEM are not in line with typical reaction conditions, especially considering electrocatalytic solid liquid interfaces, so that the active state cannot be assessed. Second, and somewhat related, is the lack of time resolution for the evaluation of alterations of the usually highly heterogeneous nanomaterials. Two methods offer a solution to these shortcomings, namely, identical location TEM (IL-TEM) and electrochemical in situ liquid TEM. The former is already well established and has delivered novel insights particularly into degradation processes; however, characterization is still performed in vacuum. The latter circumvents this issue by using dedicated in situ TEM holders but introduces extremely demanding technical challenges. Although the introduction of revolutionizing thin SiN window cells, which elegantly confine the specimen from vacuum, has allowed demonstration of the potential of the in situ approach, the reproducibility and data interpretation is still limited predominately due to the strong interaction of the electron beam with the supporting electrolyte and electrode material. Because of the importance of understanding the nanoelectrochemical structure-function relationship, this Account aims to convey a timely perspective on the opportunities and particularly the challenges in electrochemical identical location TEM and in situ liquid cell TEM with a focus on electrochemical energy conversion.